Boldine enhances bile production in rats via osmotic and farnesoid X receptor dependent mechanisms - Cermanova, Jolana; Kadova, Zuzana; Zagorova, Marie; Hroch, Milos; Tomsik, Pavel; Nachtigal, Petr; Kudlackova, Zdenka; Pavek, Petr; Dubecka, Michaela; Ceckova, Martina; Staud, Frantisek; Laho, Tomas; et al. (Toxicology and applied pharmacology, 2015)
Boldine, the major alkaloid from the Chilean Boldo tree, is used in traditional medicine to support bile production, but evidence to support this function is controversial. We analyzed the choleretic potential of boldine, including its molecular background. The acute- and long-term effects of boldine were evaluated in rats either during intravenous infusion or after 28-day oral treatment. Infusion of boldine instantly increased the bile flow 1.4-fold in healthy rats as well as in animals with Mrp2 deficiency or ethinylestradiol induced cholestasis. This effect was not associated with a corresponding increase in bile acid or glutathione biliary excretion, indicating that the effect is not related to stimulation of either bile acid dependent or independent mechanisms of bile formation and points to the osmotic activity of boldine itself. We subsequently analyzed bile production under conditions of changing biliary excretion of boldine after bolus intravenous administration and found strong correlations between both parameters. HPLC analysis showed that bile concentrations of boldine above 10 μM were required for induction of choleresis. Importantly, long-term pretreatment, when the bile collection study was performed 24-h after the last administration of boldine, also accelerated bile formation despite undetectable levels of the compound in bile. The effect paralleled upregulation of the Bsep transporter and increased biliary clearance of its substrates, bile acids. We consequently confirmed the ability of boldine to stimulate the Bsep transcriptional regulator, FXR receptor. In conclusion, our study clarified the mechanisms and circumstances surrounding the choleretic activity of boldine.
Keywords: genetická transkripce; játra; psi; signální transdukce; upregulace; Signal Transduction; Receptors, Cytoplasmic and Nuclear; Aporphines; Humans; Dogs; Multidrug Resistance-Associated Proteins; aporfiny; osmóza; hepatobiliární exkrece; Up-Regulation; potkani transgenní; protein spojený s mnohočetnou rezistencí k lékům 2; Bile; Multidrug Resistance-Associated Protein 2; Rats, Inbred Lew; Transcription, Genetic; Hepatobiliary Elimination; Female; ABC transportéry; ATP Binding Cassette Transporter, Subfamily B, Member 11; Boldine; Administration, Oral; ethinylestradiol; lidé; Bile salt export pump; zvířata; receptory cytoplazmatické a nukleární; Rats, Transgenic; cholagoga a choleretika; potkani Wistar; Glutathione; ABC transportér, podrodina B, člen 11; Hep G2 Cells; buňky MDCK; Farnesoid X receptor; transfekce; Kinetics; ženské pohlaví; Liver; buňky Hep G2; ATP-Binding Cassette Transporters; Rats, Wistar; proteiny spojené s mnohočetnou rezistencí k lékům; Madin Darby Canine Kidney Cells; Infusions, Intravenous; Bile production; glutathion; potkani inbrední LEW; Transfection; Osmosis; žluč; aplikace orální; Animals; Ethinyl Estradiol; intravenózní infuze; kinetika; Cholagogues and Choleretics